Pembelajaran IPS dalam Membentuk Sikap Anti-Bullying pada Kelas IX di PKPPS Hidayatul Qomariyah Kota Bengkulu (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Cases of Bullying in schools are becoming increasingly prevalent and risk tarnishing humanistic and educational values. Social studies education plays a crucial role as a medium for instilling character values. This study aims to describe the role of social studies education in shaping anti-Bullying attitudes among ninth-grade students at PKPPS Hidayatul Qomariyah in Bengkulu City, who have been identified as being vulnerable to Bullying by older students. This study employed a descriptive qualitative approach. Data collection was conducted through interviews, observations, and documentation. The research sample focused on key informants directly involved in the learning activities, namely the principal, the social studies teacher, and ninth-grade students at PKPPS Hidayatul Qomariyah. The collected data were then analyzed using the Miles and Huberman model. This study identified three key findings. First, during the planning stage, the teacher integrated the values of empathy and tolerance into the social studies teaching materials. Second, the learning process utilized active methods such as case studies and role-playing, allowing students to directly experience the impact of Bullying. Third, social studies instruction was shown to transform students’ social behavior, making them more compassionate, courageous in protecting victims, and respectful of one another. Social studies instruction is highly effective in shaping students’ character and fostering a harmonious school environment. Consequently, educational institutions have adopted an integrative approach in social studies as a primary tool to prevent social deviance and ensure a safe and inclusive school environment.